2018
DOI: 10.2147/tcrm.s146218
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative intervention between pharmacists and physicians on elderly patients: a randomized controlled trial

Abstract: BackgroundThe elderly population is the largest consumer of medications as this age group is at high risk for developing chronic diseases. However, medication use among elderly people is complicated by an increased risk of drug-related problems. Therefore, the present study was conducted to investigate the effects of collaborative interventions between pharmacists and physicians on health-related outcomes of elderly patients.Patients and methodsThis was a randomized controlled trial (RCT) conducted on elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…The 27 studies included in the systematic review represented a pool of 37,249 patients, 29,342 of whom were further included in the meta-analysis. Fourteen studies were conducted in the Central region of Malaysia [6,13,[16][17][18][19][20][21][22][23][24][25][26][27], three in the Northern [14,28,29] and Eastern Regions each [11,30,31], and one in Borneo [15]. Three of them were nationwide studies [32][33][34], while the remaining three studies did not specify the participants' regions [35][36][37].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 27 studies included in the systematic review represented a pool of 37,249 patients, 29,342 of whom were further included in the meta-analysis. Fourteen studies were conducted in the Central region of Malaysia [6,13,[16][17][18][19][20][21][22][23][24][25][26][27], three in the Northern [14,28,29] and Eastern Regions each [11,30,31], and one in Borneo [15]. Three of them were nationwide studies [32][33][34], while the remaining three studies did not specify the participants' regions [35][36][37].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The prevalence of polypharmacy reported in Malaysia widely varied from 45.9% to 80.6% [11][12][13], while almost one-third of the elderly in the country are using PIMs [13,14]. Nonadherence to treatment was also reported in more than half of Malaysian elderly [15]. Nearly 60% of the elderly also regularly consume supplements [13], while approximately one-fifth of them use CAM [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the benefit of a pharmacist/physician collaborative practice model in improving the management of chronic diseases such as hypertension, dyslipidemia, arrhythmias, heart failure, diabetes, asthma, osteoporosis, and psychiatric disorders. The benefits of collaboration include increased medication appropriateness, decreased occurrence of medication-related problems, medication errors and adverse drug reactions, increased communication with patients, improved patients' medication knowledge and adherence, decreased morbidity and mortality, improved patient health outcomes, reduced physician workload, and decreased healthcare costs [11][12][13][14][15][16][17][18][19]. As a result of this mounting evidence, there is a growing call for increased pharmacist-physician collaboration [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 With aging, the prevalence of diseases and geriatric syndromes increases; as a consequence, the elderly population is more frequently exposed to complex medication regimens and increased drug use. [2][3][4][5] Polypharmacy increases the risk of drug-related problems (DRPs), potentially inappropriate use of medications (PIMs), and hospitalizations, all of which are common among elderly people. 2,3,6,7 A DRP is defined as "an event or circumstance involving drug therapy that actually or potentially interferes with desired health outcomes".…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have found that pharmacists provide added value in resolving and preventing DRPs in settings such as outpatient clinics, acute care in inpatients, nursing homes, and palliative care. 5,[11][12][13][14][15][16][17][18] Studies from inpatient settings have also shown that including a pharmacist as a member of the interdisciplinary health care team may improve outcomes and decrease drug-related readmissions and mortality in geriatric patients. 2,17,[19][20][21] As team members, pharmacists offer an additional perspective in the application of medication reviews, resulting in an increase in detection of DRPs and a reduction of polypharmacy in elderly inpatients.…”
Section: Introductionmentioning
confidence: 99%